Analysis of Electromagnetic Depth Sounding Responses Over a Layered Earth: Investigating Oil & Gas Seeps in the Petroleum Provinces - Nimmagadda, Shastri; Ochan, Andrew (CSIRO, 2016)
The present work embodies the results of theoretical and practical investigations of electromagnetic depth sounding using central frequency sounding (CFS) system over a layered earth. Failure of conventional electrical resistivity sounding in the study of geological conditions under resistive overburden calls for variable frequency sounding techniques. Electromagnetic depth sounding which involves the measurement of variation in conductivity with depth is used for solving various geoengineering, hydrogeological and shallow cases of oil & gas seeps associated with stratified earth. The CFS, which is one of the depth sounding techniques involving the measurement of vertical component of magnetic field induced at the centre of a circular or square loop, is considered in the present study for obtaining theoretical responses over a layered earth and its interpretation with shallow oil and gas seeps. Because of some limitations of contour integration and numerical integration approaches, used earlier, a more rapid digital linear filter technique is adopted for evaluation of the integral involved in the CFS theoretical expressions. Theoretical expressions for frequency-domain soundings written for layered earth models are suitably transformed for evaluation through digital linear filter. Dimensionless normalized vertical magnetic field is computed for different frequencies and loop radii for layered earth models with different layer conductivities and thicknesses. The responses computed for these cases are analysed in terms of resolution characteristics and detectability effects. In frequency-domain sounding, amplitude response curves of layer-sequences show the effect of layer conductivity, layer thickness and loop radius. Separation between individual curves on the sets for amplitude responses normally gives sufficient indications for subsurface conductivity variations of the layered earth cases. The author explores the CFS applicability and feasibility in investigating shallow oil & gas seeps in oil & gas provinces, in particular on the flanks of the rifted grabens and basin margin areas, where sediment – basement contact areas are interpreted.